2018
DOI: 10.1080/10439463.2018.1540618
|View full text |Cite
|
Sign up to set email alerts
|

Implications of police occupational culture in discriminatory experiences of senior women in police forces in England and Wales

Abstract: Implications of police occupational culture in discriminatory experiences of senior women in police forces in England and Wales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 54 publications
2
43
1
Order By: Relevance
“…In a rare international comparison of the position of women in policing, Van Ewijk (2011) points to a shared global narrative of opposition and resistance to their recruitment, entry and progression. Research also confirms an enduring "heterosexist male" police culture in the 21st century in which women police continue to experience discrimination, harassment, prejudice in undertaking their roles (Brown et al, 2019;Loftus, 2009). This is as true for countries where their number has remained persistently low as for those where their percentage has increased over time.…”
Section: Introductionmentioning
confidence: 71%
“…In a rare international comparison of the position of women in policing, Van Ewijk (2011) points to a shared global narrative of opposition and resistance to their recruitment, entry and progression. Research also confirms an enduring "heterosexist male" police culture in the 21st century in which women police continue to experience discrimination, harassment, prejudice in undertaking their roles (Brown et al, 2019;Loftus, 2009). This is as true for countries where their number has remained persistently low as for those where their percentage has increased over time.…”
Section: Introductionmentioning
confidence: 71%
“…Women’s stunted entry and retention may be attributed to a variety of internal and external factors, including gendered processes, gender socialization, and masculine police subcultures (Brown, 2007; Brown, Fleming, et al., 2019; Corsianos, 2009; Garcia, 2003; Morash & Haarr, 2012). The masculine subculture is one of the most visited factors in the literature because it is known to cultivate adverse experiences for women (Rabe-Hemp, 2009; Silvestri, 2017).…”
mentioning
confidence: 99%
“…Bea’s fear of losing respect and credibility is common and it is cited as a reason for why women might resist the introduction of quotas (Van den Brink & Stobbe, 2014). The masculine police culture already invalidates women (Brown, 2007; Brown et al, 2019; Heidensohn, 2008; Waddington, 1999), and the interviews suggested that policewomen feared that a quota system would compound negative attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…However, police organizations tended to ignore the legislation at this time (Prenzler, 2015). This is probably not surprising, considering that the occupational culture of policing has always had a strong emphasis on masculinity and this emphasis has delegitimized and excluded women (see, Brown, 2007; Brown et al, 2019; Heidensohn, 2008; Manning, 2007; Silvestri, 2003; Smith & Gray, 1985; Waddington, 1999). It was not until the Equal Opportunity Acts, which had the broader aim of providing greater opportunity for women, were legislated in the 1980s that the number of policewomen in Australia began to increase (Prenzler, 1995; Prenzler & Hayes, 2000).…”
Section: Introduction Of Equal Employment Opportunities Policies In Amentioning
confidence: 99%